NATIONAL UNITY PRIZE (International Library of African Music, 1969)
NORTHWESTERN UNIVERSITY PRESS and THE PROGRAM OF AFRICAN STUDIES OF NORTHWESTERN UNIVERSITY announce an annual prize of $1,000 for an outstanding book which contributes significantly to an understanding of national unity.
Keywords: African Music